Staycation Contract Renewal Terms: Twitter Users' Perceptions of Women Workers' Speak Up Action - Almada, Fitaqi; Regina Widhiasti, Maria; Bachrioktora, Yudi (Asian Journal of Social and Humanities, 2024)
The practice of staycation revealed in Cikarang as a condition of extending the contract is a form of sexual violence and harassment. The phenomenon of speak up is a phenomenon where survivors report and tell about sexual violence experienced. The study aimed to understand the views and reactions of Twitter social media users to sexual harassment in the workplace. Researchers used the perception analysis approach of Filebron (2017) and Stubbs-Richardson et al (2018) by collecting data through Twitter accounts @geloraco in the case of female workers in Cikarang who received sexual harassment at work. The results showed that the use of Twitter in accessing information on cases of sexual violence experienced by female labor AD on @geloraco accounts, including the form of thread replies in the form of negative and positive comments. There are supportive reactions containing affirmations, validation, sympathy, and recognition as well as unsupportive reactions that are blaming, doubtful, and demeaning to the survivor's experience.